Telomere length measures in the Northern Ireland cohort for the longitudinal study of ageing (NICOLA) - Claire Hill; Laura Smyth; Jill Kilner; Katie Quinn; Angie Scott; Charlotte Neville; Frank Kee; Bernadette McGuinness; Amy Jayne McKnight (BMC Research Notes)
Abstract Objectives Using blood derived DNA collected from individuals within the Northern Ireland COhort for the Longitudinal study of Ageing (NICOLA), quantitative real-time polymerase chain reaction (RT-PCR) based absolute telomere length measures were derived in triplicate. This data is generated on a subset of participants (n = 2,971) within the NICOLA cohort at Wave 1 baseline. NICOLA commenced Wave 3 of data collection in Autumn 2024. Data description The NICOLA study recruited approximately 8,500 people from across Northern Ireland, with individuals recruited as representative of the Northern Ireland population. At recruitment, the NICOLA cohort was 45% male and 55% female. Adults were recruited over the age of 50, with approximately 50% of participants aged between 50 and 65, and 10% of participants over the age of 80. Telomere length (TL) values were determined for 2,971individuals (47.7% male) across 33 batches using the Absolute Human Telomere Length Quantification qPCR Assay kit and Roche LightCycler 480 II. Within-batch duplicate measures were established, as were water controls and non-template controls.